2021
DOI: 10.1186/s12913-021-06620-z
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of public hospitals autonomy in Iran: from budgetary hospitals to corporate hospitals

Abstract: Background Organizational reforms of hospitals in Iran are mainly aimed at improving efficiency, reducing government spending on health care, and improving the quality of services. These reforms began with hospital autonomization and have continued with other initiatives such as formation of board of trustees, independent and corporatized hospitals. Objective The purpose of this scoping review was to summarize and compare the results of studies con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…FUCOM has fewer pairwise comparisons and MARCOS considers both anti-ideal and an ideal solution simultaneously providing more reliable results. According to the findings, income is the most vital criterion in selecting organizational modalities for hospitals and the private modality is the most appropriate organizational modality for Iranian hospitals; a fact that clearly demonstrates the growing need of the healthcare sector in Iran to exponentially integrate and comply with market and market type mechanisms either through a direct privatization initiative or a step by step scenario through autonomization or corporatization with an eye to convert hospitals to totally private entities in the long run which is supported by other results of this study which prioritize autonomous and corporate hospitals over budgetary ones [ 84 , 90 ]. An agenda which is closely aligned with IMF and world bank policies in developing countries like Iran which clearly shows the high capacity in the Iranian healthcare sector to potentially get involved in such international organizations programs and initiatives in the near future.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…FUCOM has fewer pairwise comparisons and MARCOS considers both anti-ideal and an ideal solution simultaneously providing more reliable results. According to the findings, income is the most vital criterion in selecting organizational modalities for hospitals and the private modality is the most appropriate organizational modality for Iranian hospitals; a fact that clearly demonstrates the growing need of the healthcare sector in Iran to exponentially integrate and comply with market and market type mechanisms either through a direct privatization initiative or a step by step scenario through autonomization or corporatization with an eye to convert hospitals to totally private entities in the long run which is supported by other results of this study which prioritize autonomous and corporate hospitals over budgetary ones [ 84 , 90 ]. An agenda which is closely aligned with IMF and world bank policies in developing countries like Iran which clearly shows the high capacity in the Iranian healthcare sector to potentially get involved in such international organizations programs and initiatives in the near future.…”
Section: Discussionsupporting
confidence: 74%
“…As the results of the literature review show, the most crucial recommendation is that if there is a need and also a strong will to make a change, managers and policymakers should better consider a full transition to a private organizational modality rather than shift only to a corporate or an autonomous one. It needs to be mentioned that as several studies have shown, in most cases, specially in developing countries, there is a need to bring upon the structural adjustment initiative in a step by step long-term run due to several factors like socio-economic and geopolitical aspects of each case; otherwise the initiative may result in the opposite of what is aimed for [ 84 , 90 ]. Furthermore, since there is a possibility that privatization causes an increase in health services costs, hospital managers and policymakers should pay attention to the problems and issues of the public population with lower income ensuring justice in the distribution of health services as a public right.…”
Section: Resultsmentioning
confidence: 99%
“…Iran boasts an extensive public healthcare system that facilitates essential health services to its population [ 11 ]. The government operates public hospitals and clinics, often subsidizing services to enhance affordability for the general populace [ 12 ]. The role of the private sector is also noteworthy in Iran’s healthcare system, with private hospitals, clinics and medical practitioners offering a diverse range of healthcare services [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the changes, the hospitals have faced challenges like increasing costs more than three times in recent years, which have limited access to services [ 15 ]. From a structural perspective, reforms, that mostly have happened regarding dealing with upcoming changes needed to be more comprehensive and aligned with each other or other sections of the health system [ 16 ]Human resource management also has changed regarding financing models, work processes, inter-sectoral and intra-sectoral collaboration, and performance evaluation standards [ 17 ].…”
Section: Introductionmentioning
confidence: 99%